Mercury Redox Chemistry in the Negro River Basin, Amazon: The Role of Organic Matter and Solar Light - Jardim, Wilson F.; Bisinoti, Marcia Cristina [UNESP]; Fadini, Pedro Sergio; da Silva, Gilmar Silverio (Springer, 2010)
Pristine water bodies in the Negro River basin, Brazilian Amazon, show relatively high concentrations of mercury. These waters are characterized by acidic pH, low concentrations of suspended solids, and high amounts of dissolved organic matter and are exposed to intense solar radiation throughout the year. This unique environment creates a very dynamic redox chemistry affecting the mobility of mercury due to the formation of the dissolved elemental species (Hg-0). It has been shown that in this so-called black water, labile organic matter from flooded forest is the major scavenger of photogenerated H2O2. In the absence of hydrogen peroxide, these black waters lose their ability to oxidize Hg-0 to Hg2+, thus increasing Hg-0 evasion across the water/atmosphere interface, with average night time values of 3.80 pmol m(-2) h(-1). When the dry period starts, labile organic matter inputs gradually diminish, allowing the increasing concentration of H2O2 to re-establish oxidative water conditions, inhibiting the metal flux across the water/atmosphere interface and contributing to mercury accumulation in the water column.
Keywords: Amazon; Mercury; Redox chemistry; Negro River; Solar light